AKULTURASI BUDAYA ISLAM DAN HINDU PADA SINETRON JODHA AKBAR DALAM PERSPEKTIF PENDIDIKAN ISLAM MULTIKULTURAL - Masyi’atul Maghfiroh, Diska; Khumaidi, Ahmad; Lailia Maghfiroh, Ummi (Penerbit Lafadz Jaya, 2025)
This study aims to reveal the symbolic meaning of the interaction of Islamic and Hindu cultures that occur in the soap opera Jodha Akbar and to find out the values of multicultural Islamic education that are displayed through narrative and visualization. This study uses a qualitative method with a semiotic approach to interpret cultural signs that appear in scenes, dialogues, costumes, and religious rituals that are displayed. The results of the study show that this soap opera successfully depicts a harmonious cultural acculturation process through attitudes of tolerance, mutual respect, and dialogue between the main characters. Symbols of Islamic and Hindu culture are displayed side by side without erasing each other's identities, such as in worship rituals, social systems, and traditional processions. The values of multicultural Islamic education that include getting to know each other, moderation, tolerance, cooperation, and balance are depicted through the actions and decisions of the characters, reflecting the application of the principle of peaceful coexistence in a pluralistic society